Odpowiedzi

  • Użytkownik Zadane
2010-03-23T12:37:41+01:00
A= 5⁴⁵ - 5⁴⁴
a = 5⁴⁴(5 - 1)
a = 5⁴⁴ × 4

b= 125¹⁴*²⁵
b = 125³⁵⁰
b = 5¹⁰⁵⁰

c= (5¹⁵)³
c = 5⁴⁵
c = 5⁴⁴ × 5

d= 15⁴⁴:3⁴
d³ = 5⁴⁴ × 3⁴⁴ ÷ 3⁴³
d = 5⁴⁴ × 3

b>c>a>d
2010-03-23T12:40:41+01:00
A) 5(bo odejmujesz 44 od 45 i zostaje ci 5 do potęgi 1 czyli same 5 chyba)
c) 5 do 45 (bo mnożysz 15 *3)
d) 5 do 1 potęgi (czyli chyba też 5) nie wiem czy jest to dobrze... ;P
2010-03-23T12:56:30+01:00
A = 5⁴⁵ - 5⁴⁴ = (5*5^44)-544
B= (125^3)^50 =[(53)^3]50= 5^(3*3*50)=5^450
c = (5¹⁵)³ = 5^(15*3) = 5^45
d = 15⁴⁴ ÷ 3⁴³=(3*5)^44/ 3^43=3^44/3^43 *5^44=3*5^44

A<d<c<b